2018
DOI: 10.1038/s41393-018-0217-5
|View full text |Cite
|
Sign up to set email alerts
|

Sepsis in mechanically ventilated patients with spinal cord injury: a retrospective analysis

Abstract: Study Design Retrospective analysis. Objectives Sepsis, one of the most frequent and life-threatening complications on intensive care units (ICUs), is associated with a need for mechanical ventilation (MV) as well as adverse respiratory outcomes in hospitalized individuals. However, it has poorly been investigated in patients with spinal cord injury (SCI); a population at high risk for pulmonary and infectious complications. Setting Spinal Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 39 publications
2
11
1
1
Order By: Relevance
“…There is a paucity of research on the clinical outcomes of SCI patients who require ICU care [4], [8], [30][31][32]. The mortality rate of critical SCI patients was about 10% in the current study, but other reported the mortality rate could reach 38.5% [33].…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…There is a paucity of research on the clinical outcomes of SCI patients who require ICU care [4], [8], [30][31][32]. The mortality rate of critical SCI patients was about 10% in the current study, but other reported the mortality rate could reach 38.5% [33].…”
Section: Discussioncontrasting
confidence: 54%
“…More importantly, critical SCI patients may suffer from a higher mortality due to renal failure, respiratory failure, hemodynamic instability, sepsis from urinary tract infection, life-threatening autonomic hyper-reflexia etc. [3][4][5][6][7][8] . CC-BY-NC-ND 4.0 International license It is made available under a is the author/funder, who has granted medRxiv a license to display the preprint in perpetuity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to unrelenting visceral pain, neurogenic bowel can be particularly disadvantageous to patient welfare given that complications of neurogenic bowel (i.e., autonomic dysreflexia, septicemia, etc.) account for the most prevalent causes of emergency medical treatment during the chronic stage of SCI care ( 26 29 ).…”
Section: Introductionmentioning
confidence: 99%
“…VAP increases the need for prolonged mechanical ventilation and worsens neurologic recovery, which lead to increased long-term ventilator dependence. 7,8 People with SCI surviving to one-year post injury who are ventilator dependent have approximately half the life expectancy of similarly injured individuals who are not ventilator dependent. 9 Few ventilator management strategies aiming to decrease the duration of ventilator dependence have been evaluated in SCI patients, both in the acute and sub-acute rehabilitation settings.…”
Section: Introductionmentioning
confidence: 99%